Criminal Law Policy and Implementation Challenges of Chemical Castration in Indonesia - Kodrat Alam; Hibnu Nugroho; Setya Wahyudi; Dwi Hapsari Retnaningrum; Fareed Mohd Hassan (Universitas Negeri Semarang, 2026)
This study analyzes the obstacles in implementing chemical castration as an additional sanction for perpetrators of child sexual violence in Indonesia. Using normative legal research with a statutory and conceptual approach, this study examines the limitations of regulations and institutional barriers to the implementation of chemical castration. The research findings indicate two main obstacles in the implementation of chemical castration: the lack of adequate treatment for sexual impulse disorders experienced by convicts and the refusal of doctors to act as executors of chemical castration due to ethical considerations. To address these challenges, this study proposes a reconstruction of criminal law policy by revising the mechanism for postponing the execution of chemical castration, adjusting rehabilitation measures for perpetrators deemed unfit for chemical castration, and expanding the scope of resources for chemical castration executors through police medicine. This reconstruction aims to ensure legal certainty, improve rehabilitation for convicts, and increase the effectiveness of criminal sanctions in preventing child sexual violence.